Time is Life: A Case Report on Early Cardiopulmonary Resuscitation in a Witnessed Cardiac Arrest - Hersinta Retno Martani; Rizki Puji Agustin; Abu Bakar (Universitas Pahlawan Tuanku Tambusai, 2025)
Introduction: Cardiac arrest can occur unexpectedly in a hospital setting, even in individuals who were not patients. A cardiac arrest happened at the hospital, subsequently addressed with rapid and effective intervention due to sufficient resources. Main Symptoms: A patient caregiver in the ward experienced cardiac arrest, prompting the nurse to promptly activate the code blue system. He had previously reported back pain to his wife, who was a patient in the ward at the time. Therapeutic intervention: The Code Blue team from emergency department (ED) and intensive care unit (ICU) immediately arrived to administer high-quality cardiac pulmonary resuscitation. Timely intervention and defibrillation were critical in preserving the patient’s life. The electrocardiogram obtained post-return of spontaneous circulation (ROSC) exhibited ST-segmen depression accross multiple leads. The patient was promptly transported to the ED for stabilization and scheduled for primary percutaneous coronary intervention. Conclusion: Prompt and effective cardiopulmonary resuscitation enhance patient survival rates. Subsequently, thorough and effective treatment is essential to minimize the risk of patient morbidity. Keywords: cardiopulmonary resuscitation, cardiac arrest, return of spontaneous circulation